Estudo estereológico dos vasa vasorum em artérias coronárias com diferentes graus de aterosclerose - Batigália, Fernando (2003)
Introduction: About half of the cases of atherosclerotic coronary disease (a mean of 15% of women deaths and 25% of men) cannot be explained by most of the known risk factors. Coronary vasa vasorum are associated with coronary artery disease; however, their anatomy and physiopathology are not well clear. Objective: The aim of this study was to carry out a post mortem stereological study of adventitial vasa vasorum in different histopathological degrees of coronary atherosclerosis intending to correlate vasa vasorum, myocardial infarction physiopathology and histopathological degrees of atherosclerosis. Method: Ten consecutive autopsies of adults (5 men, 5 women, from 35 to 83 years-old, frozen at 4o C) were performed. Six proximal, medium and distal biopsies of the anterior and posterior interventricular coronary branches (at intervals of 1.5 cm) were performed per autopsy (a total of 60 coronary biopsy fragments). Fragments were processed by histological routine technique and cut in 4 fragments of 4 mm thickness. The first two consecutive histological fragments were stained by hematoxylin-eosin, and the two remaining by Masson´s trichrome. The fragments were histopathologically analysed according to Stary´s coronary atherosclerosis classification and examined by Zeiss Jenaâ, a light microscope with a bright chamber attached a Zeissâ micrometer scale, to outline adventitial vasa vasorum as well as to measure the coronary intraluminal diameter and the medial thickness. Intersection points of vasa vasorum with Merzâ´s grille were manually counted. For all types of vasa vasorum, points on Merzâ´s grille were counted to obtain the following stereological parameters of vasa vasorum: diameter, wall thickness, volumetric and superficial density, and adventitial connective tissue density. Parametric data were analysed by Pearson s linear correlation and principal component analysis. Agreement in determining coronary atherosclerosis degree in laminas stained by hematoxylin-eosin or Masson´s trichrome was assessed by kappa statistics. Differences among variables at each atherosclerosis degree was assessed by analysis of variance or Kruskal-Wallis test. Results: Coronary intraluminal diameter correlated negatively with coronary medial thickness and number of adventitial vasa vasorum (r>0.50; P-value<0.05). These correlations may be explained by sex, age and coronary atherosclerosis degree (r>0.50; P-value<0.05). All stereological parameters of vasa vasorum correlated negatively with coronary intraluminal diameter and positively with medial thickness, both explained by sex and atherosclerosis degree (r>0.50; P-value<0.05). The size of all types of vasa vasorum augmented proportionally to atherosclerosis histopathological degree aggravation. Kappa statistics for hematoxylin-eosin and Masson´s trichrome presented agreements varying from substantial or good to almost perfect or fine . All variables presented significant differences since the degree II of atherosclerosis. Conclusions: Coronary medial thickness and number of vasa vasorum correlated negatively with coronary intraluminal diameter. These correlations may be explained by sex and coronary atherosclerosis degree. Stereological parameters of vasa vasorum (except coronary adventitial connective tissue density) correlated positively with number of adventitial vasa vasorum as well as medial thickness, and negatively with coronary intraluminal diameter. Both correlations were determined by degree of atherosclerosis. Venular rupture in vulnerable atherosclerotic plaques may be associated with myocardial infarction arising since the degree II of atherosclerosis.